2019
DOI: 10.1248/bpb.b18-00821
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of <i>in Vitro</i> Bactericidal Activity of 1.5% Olanexidine Gluconate, a Novel Biguanide Antiseptic Agent

Abstract: Recently, 1.5% olanexidine gluconate, a biguanide compounds, was launched as a new antiseptic agent in Japan. However, the comprehensive bactericidal spectrum of olanexidine gluconate is still unknown. In this study, we evaluated in vitro bactericidal activity of olanexidine gluconate using time-kill assay against various bacteria, mycobacteria, and fungi. With the exception of Burkholderia cepacia and Mycobacterium spp., 1.5% olanexidine gluconate exhibited fast-acting (≤60 s) bactericidal activity against al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 22 publications
4
20
0
Order By: Relevance
“…We measured growth-inhibitory effects of GSC against various bacteria and fungi using the methods that were confirmed by previous studies [10,11] (Fig. 1…”
Section: Growth-inhibitory Effects Of Gsc Against Various Bacteria Ansupporting
confidence: 63%
See 2 more Smart Citations
“…We measured growth-inhibitory effects of GSC against various bacteria and fungi using the methods that were confirmed by previous studies [10,11] (Fig. 1…”
Section: Growth-inhibitory Effects Of Gsc Against Various Bacteria Ansupporting
confidence: 63%
“…Anaerobic bacteria were cultured under the recommended conditions. Antimicrobial susceptibility and inhibitory effects against these strains were confirmed by previous study [10,11]. GSC (Lot, 2020.1/FCA IK; Iskra Co. Ltd., Tokyo, Japan) was employed as the P. oleracea formulation and contained 3 g (dry weight) of condensed P. oleracea extract per gram and no other bioactive components.…”
Section: Bacterial Strains Culture Conditions and Chemicalssupporting
confidence: 52%
See 1 more Smart Citation
“…Olanedine solution (1.5%) (pH ~5, specific gravity ~1.0), with its main component olanexidine gluconate, was launched as a new antiseptic agent in 2015, but it is currently only commercially available in Japan. Several studies 1,2,11 have demonstrated that it exhibits fast‐acting and long‐lasting antimicrobial activity. The bactericidal activity of Olanedine solution persists for 12 hours after the solution is used for antiseptic rinsing, whereas other antiseptics, such as 0.5% chlorhexidine gluconate and 10% povidone‐iodine, hardly display any long‐lasting effectiveness 11 .…”
Section: Discussionmentioning
confidence: 99%
“…It first became commercially available in Japan in 2015. It has marked bactericidal effects against a wide range of bacteria, including methicillin‐resistant Staphylococcus aureus , vancomycin‐resistant enterococci, and Pseudomonas aeruginosa 1,2 . The active ingredient of Olanedine solution is olanexidine gluconate (Figure 1) (CAS no.…”
Section: Introductionmentioning
confidence: 99%